Study on optimized adsorption chiller employing various heat and mass recovery schemes - Muttakin, Mahbubul; Islam, Md. Amirul; Malik, Kuldeep Singh; Pahwa, Deepak; Saha, Bidyut Baran (International journal of refrigeration, 2021)
•A mathematical method is developed to simulate the processes of an adsorption chiller.•The simulated outlet temperatures are within ± 0.5 °C of experimental data.•The variations of uptake and bed temperature throughout the cycle are investigated.•Optimum mass and heat recovery durations for different operating temperatures are determined.•A nominal mass recovery may be sufficient for low generation temperature lift. A typical commercial two-bed adsorption chiller using silica gel as adsorbent and water as adsorbate is simulated in the current study. Each of the two beds goes through four processes in one cycle, namely, adsorption, mass recovery, heat recovery, and desorption. A transient lumped analytical model is developed, and the governing equations are solved using the MATLAB® platform. The thermophysical properties of the refrigerant are collected from REFPROP®, which is integrated within the MATLAB® codes. The simulation model is validated with the test results of a commercial chiller manufactured by Bry-Air (Asia) Pvt. Ltd. The cooling capacity of the chiller is 40 ton of refrigeration, and in this study, the simulation results are in good agreement with the test results provided by the manufacturer. The simulation model is then utilized in the present investigation to predict the performance of a typical commercial chiller under various working conditions. The recovery times, the temperatures of hot water, cooling water, and chilled water are varied, and their impacts on the cooling capacity and COP of the chiller are analyzed. The optimum recovery durations are reported for different temperatures, and their effects on the bed uptakes are investigated. The model can be used as an effective means to determine the optimal cycle time with necessary recovery durations for a specific cooling load, with a view to providing the maximum efficiency under specified operating conditions.